2023
DOI: 10.3390/jcm12113825
|View full text |Cite
|
Sign up to set email alerts
|

Early Loading of Two Implants Supporting Mandibular Overdentures in Geriatric Edentulous Patients: A 12-Year Follow-Up Study

Abstract: Background: This study aims to show the clinical outcomes of implants supporting mandibular overdentures in edentulous patients. Methods: Mandibular edentulous patients were diagnosed with an oral examination, panoramic radiograph, and diagnostic casts for intermaxillary relations and treated with overdentures over two implants. After two-stage surgery, implants were early loaded with an overdenture at 6 weeks. Results: Fifty-four patients (28 females and 24 males) were treated with 108 implants. Thirty-two pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…According to conventional protocols, implants should not be loaded throughout the osseointegration phase, typically lasting 3‒4 months for the mandible and 6‒8 months for the maxilla. 9 , 10 Bone healing increases the contact between the implant and the surrounding bone after insertion. An implant may fail if loaded before this contact reaches a particular point.…”
Section: Introductionmentioning
confidence: 99%
“…According to conventional protocols, implants should not be loaded throughout the osseointegration phase, typically lasting 3‒4 months for the mandible and 6‒8 months for the maxilla. 9 , 10 Bone healing increases the contact between the implant and the surrounding bone after insertion. An implant may fail if loaded before this contact reaches a particular point.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies with overdentures and fixed complete prostheses have shown that implant treatment in older people can be a successful possibility for the rehabilitation of edentulous patients [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%